Case Report: A Novel Non-Canonical Splice Site Variant (c.1638+7T>C) in TRPM6 Cause Primary Homagnesemia With Secondary Hocalcemia - Song, Jiayu; Lei, Juan; Zhang, Jianxia; Zhang, Aiqing; Gan, Weihua; Zheng, Bixia; Wang, Chunli; Gong, Jing (Frontiers in Pediatrics, 2022)
Objective Primary hypomagnesemia with secondary hypocalcemia (HSH) is caused by loss-of-function mutations in the TRPM6 gene encoding the epithelial magnesium channel. It is characterized by hypomagnesemia and secondary hypocalcemia associated with neurological symptoms. Here, we aimed to investigate the genetic defects of the TRPM6 gene in a girl from China. Methods The genomic DNA of the proband and the parents was extracted for whole-exome sequencing (WES). Sanger sequencing was further performed to validate the candidate variants. Subsequently, the TRPM6 gene deletion was verified by quantitative PCR (qPCR) experiment. The effect of the variant on mRNA splicing was analyzed through a minigene splice assay and reverse transcription PCR (RT-PCR) in vitro. Results The proband presented with the symptoms of generalized seizures, tetany, and muscle spasms, which were refractory to anticonvulsant treatment. Phenotypic data indicated that the patient had hypomagnesemia, poor parathyroid hormone (PTH) response, and resultant hypocalcemia. The trio whole-exome sequencing identified that the proband carried compound heterozygous variants in the TRPM6 gene, a paternally derived exon 6 deletion, and a maternally derived splicing variant (c.1638+7T>C) in exon 14. The minigene splice assay confirmed that the c.1638+7T>C variant resulted in exon 14 skipping, which caused the alteration of TRPM6 mRNA splicing. Conclusion Our results support that the compound heterozygous variants in TRPM6 are responsible for HSH in this patient. A novel pathogenic splicing variant (c.1638+7T>C) in the intron 14 disturbs the normal TRPM6 mRNA splicing, suggesting that the non-classical splice variant plays a critical role in HSH. This variant is essential for future effective genetic diagnosis.